Nutritional assessment of Oraons of West Bengal: a comparison between biochemical and anthropometric methods - Bhattacharya, Ankita; Mukherjee, Shankarashis; Kumar Roy, Subrata (Anthropological Review, 2019)
Comprehensive nutritional assessment is the basis of nutritional diagnosis and necessary to identify the individual or the population at a risk of dietary deficiencies. However, there is no specific and confirmatory method to measure nutritional status. Present study tried to find out the efficacy of two nutritional assessment method (1) biochemical test like Total serum protein (TSP) and (2) anthropological measurements like body mass index (BMI) and mid-upper-arm-circumference (MUAC). Later, three methods were tested and compared for the strength of assessing the nutritional status. Study was conducted among 198 adult Oraon, 84 male, 114 female individuals of Madarihat and Falakata police station area, Alipurduar district, West Bengal. Selected blood parameters such as total serum protein (TSP), serum albumin and haemoglobin and anthropometric measurements (height, weight, mid-upper arm circumference, waist circumference, hip circumference, calf circumference, biceps skinfold, triceps skinfold, and calf skinfold) were obtained following standard instruments and protocols. Nutritional status of all individuals was assessed by TSP, BMI and MUAC classification methods. Comparison between/among three classification methods (TSP, BMI and MUAC) was done and discriminant function analysis was adopted to find out the percentage of correct classification by each methods. It was found that prevalence of undernutrition using TSP classification was 38.1% male and 43.0% female; using BMI was 34.5% male and 53.5% female; using MUAC was 45.2% male and 64.9% female. Discriminant function analysis showed that BMI (97.0%) had the highest capability of correct classification followed by MUAC (84.80%) and TSP (63.60%). Results indicate that however, TSP is an objective way of nutritional assessment, but BMI had the highest capability of correct classification of nutritional status. It may be pointed out that the evaluation with TSP was expensive and invasive whereas BMI is non-expensive and completely a non-invasive way of evaluation. Therefore, BMI may widely be used for nutritional assessment.